2019
DOI: 10.1111/joim.13002
|View full text |Cite
|
Sign up to set email alerts
|

The hospital frailty risk score in patients with heart failure is strongly associated with outcomes but less so with pharmacotherapy

Abstract: Background Although frailty is known to be an important prognostic factor in heart failure (HF), HF risk‐adjustment models do not incorporate frailty measures and the interplay between frailty, age and pharmacotherapy is unclear. Objectives To explore the relationships between frailty, pharmacotherapy and outcomes in heart failure (HF). Methods Retrospective cohort study of all adults in Alberta, Canada hospitalized for the first time for HF between 2004 and 2016. Frailty was defined using the Hospital Frailty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 24 publications
8
28
0
1
Order By: Relevance
“…A fair to moderate level of agreement between frailty assessment methods is not uncommon and our very recent direct comparison of hospitalised patients 65 years and over, also identified low correlation between eFI and HFRS 13 , 28 . Consistent with previous studies, we observed significantly poorer outcomes with higher categories of frailty for eFI and HFRS among hospitalised patients – including those admitted to ICU—with the HFRS discriminating to a slightly greater degree than eFI 5 , 29 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A fair to moderate level of agreement between frailty assessment methods is not uncommon and our very recent direct comparison of hospitalised patients 65 years and over, also identified low correlation between eFI and HFRS 13 , 28 . Consistent with previous studies, we observed significantly poorer outcomes with higher categories of frailty for eFI and HFRS among hospitalised patients – including those admitted to ICU—with the HFRS discriminating to a slightly greater degree than eFI 5 , 29 .…”
Section: Discussionsupporting
confidence: 91%
“…Whilst CCI is derived using ICD-10 codes of 17 comorbidities, the HFRS was developed giving weighting to 109 frailty-related ICD-10 codes depending on their association with frailty 13 , 21 . In a recent study in heart failure patients only moderate agreement was found between CCI and HFRS, although both scores were predictive of outcome 29 .…”
Section: Discussionmentioning
confidence: 85%
“…Two recent studies using the same FI (the Hospital Frailty Risk Score) in patients hospitalized with HF have shown that frailty is also associated with higher rates of short and long-term mortality after discharge; a third confirmed the distinction between frailty and comorbidity by demonstrating a poor correlation between the Hospital Frailty Risk Score and the Charlson Comorbidity Index. [42][43][44] Frailty may also reduce a patient's ability to self-care and impair adherence because of associated cognitive impairment. [36][37][38] Polypharmacy increased with increasing frailty, not only causing concerns about adherence but also about drug-related adverse effects and interactions.…”
Section: Recurrent Non-cv Hospitalizationsmentioning
confidence: 99%
“…Whilst CCI is derived using ICD-10 codes of 17 comorbidities, the HFRS was developed giving weighting to 109 frailty-related ICD-10 codes depending on their association with frailty 1321 . In a recent study in heart failure patients only moderate agreement was found between CCI and HFRS, although both scores were predictive of outcome 29 .…”
Section: Discussionmentioning
confidence: 85%